Penanganan dan Pengolahan Sampah Rumah Tangga di Kampung Bedas Desa Wangisagara Kecamatan Majalaya Kabupaten Bandung - Sopian, Sopi (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
Disposal of rubbish carelessly or around the house is still common in the Bedas village of Wangisagara Village. This makes the environment less pleasing to the eye and becomes a nest for disease if left unchecked. Therefore, it is necessary to take action to reduce careless waste disposal. This observational analytical research aims to examine household waste management and correlated factors, as well as plan community-based household waste management. Based on the results of observations, it was found that the amount of waste produced by each house in Bedas Village, Wangisagara Village varies, consisting of plastic waste. and organic. Household waste management in Bedas village, Wangisagara Village has not been implemented optimally. The suggestions given include improving waste services, forming a special village waste team, involving residents in activities as well as in financing waste activities, as well as strict sanctions if there are waste violations.